CDK4 phosphorylation status and a linked gene expression profile predict sensitivity to palbociclib - Eric Raspé; Katia Coulonval; Jaime M Pita; Sabine Paternot; Françoise Rothé; Laure Twyffels; Sylvain Brohée; Ligia Craciun; Denis Larsimont; Véronique Kruys; Flavienne Sandras; Isabelle Salmon; et al. (EMBO Molecular Medicine)
Abstract Cyclin D‐CDK4/6 are the first CDK complexes to be activated in the G1 phase in response to oncogenic pathways. The specific CDK4/6 inhibitor PD0332991 (palbociclib) was recently approved by the FDA and EMA for treatment of advanced ER‐positive breast tumors. Unfortunately, no reliable predictive tools are available for identifying potentially responsive or insensitive tumors. We had shown that the activating T172 phosphorylation of CDK4 is the central rate‐limiting event that initiates the cell cycle decision and signals the presence of active CDK4. Here, we report that the profile of post‐translational modification including T172 phosphorylation of CDK4 differs among breast tumors and associates with their subtypes and risk. A gene expression signature faithfully predicted CDK4 modification profiles in tumors and cell lines. Moreover, in breast cancer cell lines, the CDK4 T172 phosphorylation best correlated with sensitivity to PD0332991. This gene expression signature identifies tumors that are unlikely to respond to CDK4/6 inhibitors and could help to select a subset of patients with HER2‐positive and basal‐like tumors for clinical studies on this class of drugs.